Perception of Facial Emotion in Adults with Bipolar or Unipolar Depression and Controls - Schaefer, Kathryn L. (2010)
Previous research indicates that patients with depression display deficits in their ability to perceive emotions. However, few studies have used animated facial stimuli or explored sensitivity to facial expressions in depressed individuals. Moreover, limited research is available on facial processing in unipolar versus bipolar depression. In this study, 34 patients with DSM-IV major depressive disorder (MDD), 21 patients with DSM-IV bipolar disorder (BPD) in the depressed phase, and 24 never-depressed controls completed the Emotional Expression Multimorph Task, which presents facial emotions in gradations from neutral to 100% emotional expression (happy, sad, surprised, fearful, angry, and disgusted). Groups were compared in terms of sensitivity and accuracy in identifying emotions. Our preliminary findings suggest that subjects with bipolar depression may have emotional processing abnormalities relative to controls.